Game - Lyga, Barry (Lyga, Barry. I hunt killers trilogy, 2013)
After solving a deadly case in the small town of Lobo's Nod, seventeen-year-old Jazz, the son of history's most infamous serial murderer, travels to New York City to help the police track down the Hat-Dog Killer.